Response of plants to cadmium stress (International Journal of Biology and Chemistry, 2020)
In this article we discuss cadmium pollution in the environment and the various ways plants take up cadmium and respond to its accumulation. The increased development of metallurgical and mining industries is primarily responsible for the increases in cadmium pollution in the environment. Another significant source of cadmium contamination of agricultural plants is the widespread use of phosphorus fertilizers, which contain cadmium. Cadmium reduces the growth and development of plants. Cadmium in the soil also competes with the basic essential mineral elements thereby reducing their uptake by plants. This article reviews the published data on the cellular and molecular mechanisms of cadmium uptake by plants, its metabolic transformations, effects on nutrient status of plants, modulation of cadmium response by polyamines and amino acids, and the growth of plants. Strategies to reduce cadmium uptake and accumulation are also discussed.